2022
DOI: 10.3389/fgene.2022.850089
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Competitive Endogenous Mechanism and Survival Prognosis of Serum Exosomes in Ovarian Cancer Patients Based on Sequencing Technology and Bioinformatics

Abstract: Background: We determined the competitive endogenous in serum exosomes of ovarian cancer patients via sequencing technology and raw signal analysis. We performed an in-depth study of the potential mechanisms of ovarian cancer, predicted potential therapeutic targets and performed survival analysis of the potential targets.Methods: Serum exosomes from three ovarian cancer patients were used as the experimental group, serum exosomes from three patients with uterine fibroids were used as the control group, and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Recently, molecular biomarkers including lncRNA, miRNAs and mRNA can be used for detection, diagnosis, recurrence prediction and post-treatment monitoring of BC [ 6 , 7 , 8 , 9 ]. Moreover, it has been found that the lncRNAs could interact with miRNAs as competing endogenous RNA (ceRNA) to regulate BC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular biomarkers including lncRNA, miRNAs and mRNA can be used for detection, diagnosis, recurrence prediction and post-treatment monitoring of BC [ 6 , 7 , 8 , 9 ]. Moreover, it has been found that the lncRNAs could interact with miRNAs as competing endogenous RNA (ceRNA) to regulate BC.…”
Section: Introductionmentioning
confidence: 99%
“…In triple-negative breast cancer, a miR-432-p/CCDC58 regulatory axis influenced tumor proliferation, migration, and invasion phenotypes 13 . CCDC58 had also been identified as a gene associated with tumor progression in endometrial cancer and ovarian cancer 14,15 . Among the differentially expressed genes between diabetic patients and normal controls, CCDC58 ranked in the top ten, suggesting that CCDC58 might be related to the occurrence and development of diabetes 16 .…”
mentioning
confidence: 99%